Contemporary Issues in Women's Health. Issue 1 (7th June 2019) - Geary, Michael; Chibwesha, Carla; Stringer, Elizabeth
Abstract : Should we be performing routine salpingectomy as a preventative approach to reduce the risk of ovarian cancer? Machine Learning in Women's Health Women who undergo cesarean delivery in many parts of Africa are at high risk of severe maternal morbidity and mortality